Hard alloy, preparation method thereof and application of hard alloy in hard alloy cutter

By optimizing the components and particle size combinations of vanadium carbide, ruthenium and tantalum carbide in cemented carbide, combined with the hydrogen sintering process, the problems of hardness difference and magnetic coercive difference in cemented carbide tools at high temperatures are solved, and high Hardness, long life and good wear resistance.

CN119194196APending Publication Date: 2024-12-27ZHEJIANG HENGCHENG CEMENTED CARBIDE CO LTD

Patent Information

Application Number
CN202411209684.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The hardness difference and magnetic coercive force difference at high temperatures are difficult to control, affecting large-scale production, and lacking wear resistance and service life.

Method used

Vanadium carbide, ruthenium and tantalum carbide are used as regulators to optimize their mass ratio and particle size combinations, combined with hydrogen sintering process, cemented carbide with excellent strength and toughness is prepared for tool manufacturing.

Benefits of technology

It significantly improves the hardness, phase stability and processing deformation ability of the alloy, extends the service life, and forms a stable and dense metal oxide layer, enhancing corrosion resistance.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the field of hard alloy, and provides hard alloy, a preparation method thereof and application of the hard alloy in a hard alloy cutter. The hard alloy comprises the following components in every 100 parts by mass: 8-15 parts of a binder; the conditioning agent is prepared from vanadium carbide, ruthenium and tantalum carbide according to the mass ratio of (1 to 6) to (5 to 8) to 10; and the balance of tungsten carbide. The preparation method comprises the following steps: ball milling, drying and granulating, compression molding and hydrogen sintering. The hard alloy with excellent strength and toughness is obtained by optimizing the components and limiting the dosage of each component, and the service life is long when the hard alloy is applied to a blade.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of cemented carbide, in particular to a cemented carbide and a preparation method thereof and application in cemented carbide cutting tools. Background Art

[0002] Cemented carbide is an alloy material made of hard compounds of refractory metals and bonding metals through powder metallurgy. Cemented carbide has a series of excellent properties such as high hardness, wear resistance, good strength and toughness, heat resistance, corrosion resistance, etc., especially its high hardness and wear resistance, which remain basically unchanged even at a temperature of 500°C, and still have a high hardness at 1000°C. Cemented carbide is widely used as tool materials, such as turning tools, milling cutters, planers, drill bits, boring tools, etc., for cutting cast iron, non-ferrous metals, plastics, chemical fibers, graphite, glass, stone and ordinary steel. It can also be used to cut difficult-to-process materials such as heat-resistant steel, stainless steel, high manganese steel, tool steel, etc.

[0003] For example, patent CN109790076B discloses a rock drill blade, which includes: a hard component composed of tungsten carbide (WC) in a binder phase including Co, wherein the cemented carbide includes 4-18wt% Co and the balance WC and inevitable impurities, characterized in that the cemented carbide also includes Cr, the amount of Cr makes the Cr / Co mass ratio in the range of 0.04-0.19, and the difference between the hardness at a depth of 0.3mm at any point on the surface of the rock drill blade and the hardness of the main part of the rock drill blade is at least 40HV3. Although a blade with better performance is obtained, the hardness difference and magnetic coercivity difference need to be strictly controlled, which is not conducive to mass production. Therefore, an ideal solution is needed. Summary of the invention

[0004] The invention provides a cemented carbide and a preparation method thereof and application in a cemented carbide tool. By optimizing components and limiting the amount of each component, a cemented carbide with excellent strength and toughness is obtained, and the cemented carbide has a long service life when applied to a blade.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions: A cemented carbide, comprising per 100 parts by mass: 8-15 parts of binder; 0.5-3 parts of a regulator, consisting of vanadium carbide, ruthenium and tantalum carbide in a mass ratio of (1-6):(5-8):10; The balance is tungsten carbide.

[0006] Preferably, the mass ratio of vanadium carbide, ruthenium and tantalum carbide is (2-5):(6-8):10.

[0007] Preferably, the average particle size of tungsten carbide powder is 0.6-1 μm, the particle size of ruthenium is lower than that of tungsten carbide, the particle size of tantalum carbide is similar to that of tungsten carbide, and the particle size of vanadium carbide is larger than that of tungsten carbide. Further preferably, the average particle size of vanadium carbide powder is 1-5 μm, the average particle size of ruthenium powder is 20-100 nm, and the average particle size of tantalum carbide powder is 500-800 nm.

[0008] Preferably, the binder is selected from one or more of Co, Ni and Mo powders.

[0009] Preferably, the average particle size of the binder is 0.5-2 μm.

[0010] The invention also provides a method for preparing the hard alloy, comprising the following steps: ball milling, drying and granulating, pressing and forming, and hydrogen sintering.

[0011] Preferably, the ball milling uses n-hexane as the medium, the ball milling speed is 20-40 r / min, and the ball milling time is 20-40 h.

[0012] Preferably, during ball milling, tungsten carbide, a binder and tungsten carbide grinding balls with a diameter of 2-5 mm are first added and ball milled for 6-10 hours; then vanadium carbide is added and ball milled for 2-4 hours; finally ruthenium, tantalum carbide and tungsten carbide grinding balls with a diameter of 0.2-0.5 mm are added and ball milled.

[0013] Preferably, the dry granulation is carried out by spray drying.

[0014] Preferably, the sintering steps are as follows: (1) Raise the temperature to 500°C at a rate of 2-5°C / min and keep at this temperature for 2-3h; (2) Raise the temperature to 700°C at a rate of 2-5°C / min and keep at this temperature for 0.5-1h; (3) Raise the temperature to 1350-1500°C at a rate of 8-13°C / min and keep at this temperature for 1-2h; (4) Quickly cool to room temperature.

[0015] The present invention also provides the application of the cemented carbide in cemented carbide tools, which include cemented carbide milling tools and cemented carbide turning tools. The cemented carbide is pressed into a blade shape and then sintered to obtain a blank, and the blade edge of the blank is processed into a certain R angle.

[0016] Therefore, the beneficial effects of the present invention are as follows: the present invention uses vanadium carbide, ruthenium and tantalum carbide as regulators at the same time, which has a significant gain effect, wherein ruthenium inhibits the growth of tungsten carbide grains (especially abnormal growth) and promotes the transformation of the metastable α-Co of the binder cobalt to the room temperature stable ε-Co; tantalum carbide forms solid solutions and intermetallic precipitates, and these compounds and precipitates significantly improve the strength, phase stability and processing deformation ability of the alloy; vanadium carbide has a stable structure and a strong secondary hardening effect, which has a significant effect on improving hardness; and vanadium can form a stable and dense metal oxide layer in the alloy, thereby improving the corrosion resistance of the alloy and extending the service life of the alloy. DETAILED DESCRIPTION

[0017] The technical solution of the present invention is further described below through specific embodiments.

[0018] In the present invention, unless otherwise specified, the raw materials and equipment used can be purchased from the market or are commonly used in the art. The methods in the embodiments, unless otherwise specified, are all conventional methods in the art. Unless otherwise specified, parts are all weight parts, temperatures are expressed in ° C or at ambient temperature, and pressures are atmospheric pressure or near atmospheric pressure. There are many variations and combinations of reaction conditions (such as component concentrations, desired solvents, solvent mixtures, temperatures, pressures, and other reaction ranges) and conditions that can be used to optimize the purity and yield of the product obtained by the method, and only reasonable routine experiments will be required to optimize such method conditions.

[0019] Example 1. Cemented Carbide Each 100 parts by mass contains: 8-15 parts of a binder, selected from one or more of Co, Ni, and Mo powders, with an average particle size of 0.5-2 μm; 0.5-3 parts of a regulator, composed of vanadium carbide, ruthenium and tantalum carbide in a mass ratio of (1-6):(5-8):10 (more preferably (2-5):(6-8):10); the average particle size of the vanadium carbide powder is 1-5 μm, the average particle size of the ruthenium powder is 20-100 nm, and the average particle size of the tantalum carbide powder is 500-800 nm; The remainder is tungsten carbide powder with an average particle size of 0.6-1 μm.

[0020] The binder can provide toughness and impact resistance, and is used to balance the hardness and wear resistance of the alloy. The functions of the regulators vanadium carbide, ruthenium and tantalum carbide recorded in the prior art are to prevent the growth of tungsten carbide grains during the sintering process, play a role in refining the grains, and improve the high temperature hardness, high temperature strength and wear resistance of the cemented carbide. The present invention has a significant gain effect through the mutual cooperation of the three.

[0021] ① Vanadium carbide is a black cubic crystal with a melting point of 2810℃, a boiling point of 3900℃, and a relative density of 5.77. Vanadium can enhance wear resistance and oxidation resistance. Vanadium is a metal element used to enhance the wear resistance and oxidation resistance of cutting tools, which can improve the performance of cutting tools in high temperature and high strength processing. Vanadium can refine grains, stabilize the structure, and has a strong secondary hardening effect, which has a significant effect on improving hardness. Vanadium can form a stable and dense metal oxide layer in the alloy, thereby improving the corrosion resistance of the alloy and extending the service life of the alloy. However, excessive addition will affect the processability and toughness of the alloy.

[0022] ② The metal crystal structure of ruthenium is hexagonal, with a melting point of 2334°C, a boiling point of 4150°C, and a density of 12.45 g / cm at room temperature. 3 . Ruthenium has great hardness and strong wear resistance; it is very stable and has strong corrosion resistance. The addition of ruthenium will promote the solid solution of tungsten in the binder (cobalt), resulting in a serious imbalance between tungsten and carbon in the cobalt phase, inhibiting the "precipitation" of tungsten carbide grains and preventing the growth of tungsten carbide grains. Therefore, the addition of ruthenium can inhibit the growth of tungsten carbide grains, especially the abnormal growth of tungsten carbide grains. After adding ruthenium, the binder structure will also change. Ruthenium will be dissolved into the binder cobalt during the liquid phase sintering process, promoting the transformation of the metastable α-Co of cobalt to the room temperature stable ε-Co, and improving the toughness and hardness of cemented carbide.

[0023] ③Tantalum carbide has the advantages of high melting point (3880℃), high hardness (2100HV0.05), good chemical stability and strong thermal conductivity. Tantalum is a rare metal with high melting point and good thermal conductivity. It can improve the wear resistance, heat resistance and corrosion resistance of the tool, and is especially suitable for high temperature and heavy-load cutting environments. Tantalum also has the characteristics of low hardness, rich ductility (can be drawn into filaments), small thermal expansion coefficient and strong toughness, so the amount needs to be within a reasonable range. The addition of tantalum can form tantalum carbide, solid solution and intermetallic precipitates. These compounds and precipitates significantly improve the strength, phase stability and processing deformation ability of the alloy. In addition, the addition of tantalum can also improve the mechanical properties of the alloy by refining the grains and reducing the ductile-brittle transition temperature, so that it maintains toughness at room temperature.

[0024] Moreover, the particle sizes of the three can only play the best effect within the preferred range. The minimum particle size of ruthenium powder is 20-100nm, the particle size of tantalum carbide and tungsten carbide powder is between 500-1μm; the maximum particle size of vanadium carbide powder is 1-5μm. The advantages of this setting are: the smaller the particle size, the shorter the center distance, the smaller the pore size in the sintered body, and the greater the capillary force of the liquid; and the smaller the particle size, the larger the surface area, the faster the solid phase diffusion rate and the dissolution-precipitation rate after the liquid phase appears. On the one hand, the arrangement of different particle sizes of each component can gradually fill the pores, and the sintered alloy has a high density; on the other hand, the ruthenium of the present invention is first dissolved and precipitated, which inhibits the growth of tungsten carbide grains (especially abnormal growth) and promotes the transformation of the metastable α-Co of cobalt to the room temperature stable ε-Co; then tantalum carbide is dissolved and precipitated along with tungsten carbide, and tantalum carbide will form a solid solution and intermetallic precipitates, and these compounds and precipitates significantly improve the strength, phase stability and processing deformation ability of the alloy; finally, vanadium carbide stabilizes the structure and has a strong secondary hardening effect, which has a significant effect on improving the hardness; and vanadium can form a stable and dense metal oxide layer in the alloy, thereby improving the corrosion resistance of the alloy and extending the service life of the alloy.

[0025] 2. Preparation method of cemented carbide The following steps are involved: (1) Ball milling: Use n-hexane as the medium, the ball milling speed is 20-40r / min, and the ball milling time is 20-40h. When ball milling, first add tungsten carbide, binder and tungsten carbide grinding balls with a diameter of 2-5mm, and ball mill for 6-10h; then add vanadium carbide and ball mill for 2-4h; then add ruthenium, tantalum carbide and tungsten carbide grinding balls with a diameter of 0.2-0.5mm, and finally add 2-3wt% paraffin wax for ball milling (ball to material ratio 4:1). The amount of each component is referred to the amount described in part 1.

[0026] Grinding the raw materials with two kinds of grinding balls with different hardness and particle size can significantly reduce the reaction activation energy, refine the grains, enhance the powder activity, and improve the sintering ability. The obtained powder has stable quality, uniform particle size, high ball formation rate, and high loose density, which is beneficial to subsequent molding and sintering.

[0027] The present invention performs ball milling in batches according to the particle size of each component, and the obtained powder has a higher loose density.

[0028] (2) Drying and granulation: conventional spray drying method is used.

[0029] (3) Pressing: using conventional methods.

[0030] (4) Hydrogen sintering: The sintering steps are as follows: 1) heating to 500°C at a rate of 2-5°C / min and keeping warm for 2-3h; 2) heating to 700°C at a rate of 2-5°C / min and keeping warm for 0.5-1h; 3) heating to 1350-1500°C at a rate of 8-13°C / min and keeping warm for 1-2h; 4) rapidly cooling to room temperature to obtain cemented carbide.

[0031] According to the components of the present invention, a specific sintering temperature is adopted, and the obtained alloy has good performance. The temperature is slowly increased in the early stage, so that the contact stress between the powder particles is gradually eliminated, and the surface diffusion is uniform. The heating rate is increased in the later stage to promote the crystallization transformation and form the basic organization and structure of the skeleton alloy. Rapid cooling can not only inhibit the precipitation of tungsten carbide from cobalt, but also retain more tungsten carbide in the bonding phase to strengthen the bonding phase, and round the WC grains to become spherical bodies with wavy crystal surfaces. The hardness does not change much, but the strength and toughness can be improved.

[0032] 3. Application of cemented carbide The cemented carbide is applied to cemented carbide tools, including cemented carbide milling tools and cemented carbide turning tools. Specifically, the step (3) in the second step is pressed into a blade shape during pressing, and the blade blank is obtained after hydrogen sintering in step (4). The blade edge of the blade blank is processed into a certain R angle to obtain a cemented carbide tool.

[0033] Example 1 A cemented carbide consisting of the following components: 10 parts by weight of a binder, specifically cobalt powder with an average particle size of 1 μm; 2 parts by weight of a regulator, consisting of vanadium carbide, ruthenium and tantalum carbide in a mass ratio of 4:7:10; wherein the average particle size of the vanadium carbide powder is 3 μm, the average particle size of the ruthenium powder is 80 nm, and the average particle size of the tantalum carbide powder is 600 nm; 88 parts by weight of tungsten carbide powder, with an average particle size of 0.8 μm.

[0034] The preparation method of the above-mentioned cemented carbide is: (1) Ball milling: n-hexane was used as the medium, the ball milling speed was 30 r / min, and the total ball milling time was 30 h. During ball milling, tungsten carbide, binder and tungsten carbide grinding balls with a diameter of 3 mm were first added according to the above components, and ball milling was performed for 8 h; then vanadium carbide was added and ball milling was performed for 3 h; then ruthenium, tantalum carbide and tungsten carbide grinding balls with a diameter of 0.4 mm were added, and finally 2 wt% paraffin wax was added and ball milling was performed for 19 h.

[0035] (2) Drying and granulation: conventional spray drying method is used.

[0036] (3) Pressing: Pressing into a blade shape using conventional methods.

[0037] (4) Hydrogen sintering: The sintering steps are as follows: first, heating to 500°C at a rate of 3°C / min and keeping at that temperature for 2 h; then heating to 700°C at a rate of 4°C / min and keeping at that temperature for 0.5 h; then heating to 1400°C at a rate of 10°C / min and keeping at that temperature for 1 h; finally, gas phase rapid cooling to room temperature to obtain cemented carbide.

[0038] The cutting edge of the cemented carbide blade is processed into an R angle to obtain a cemented carbide tool.

[0039] Example 2 A cemented carbide consisting of the following components: 8 parts by weight of a binder, specifically a mixture of cobalt powder and molybdenum powder with an average particle size of 2 μm (weight ratio 1:1); 0.5 parts by weight of a regulator, composed of vanadium carbide, ruthenium and tantalum carbide in a mass ratio of 2:6:10; wherein the average particle size of the vanadium carbide powder is 5 μm, the average particle size of the ruthenium powder is 100 nm, and the average particle size of the tantalum carbide powder is 800 nm; 91.5 parts by weight of tungsten carbide powder, with an average particle size of 1 μm.

[0040] The preparation method of the above-mentioned cemented carbide is: (1) Ball milling: n-hexane is used as the medium, the ball milling speed is 20r / min, and the total ball milling time is 40h. During ball milling, according to the above components, tungsten carbide, binder and tungsten carbide grinding balls with a diameter of 3mm are first added, and ball milling is carried out for 10h; then vanadium carbide is added and ball milling is carried out for 4h; then ruthenium, tantalum carbide and tungsten carbide grinding balls with a diameter of 0.4mm are added, and finally 3wt% paraffin wax is added and ball milling is carried out for 26h.

[0041] (2) Drying and granulation: conventional spray drying method is used.

[0042] (3) Pressing: Pressing into a blade shape using conventional methods.

[0043] (4) Hydrogen sintering: The sintering steps are as follows: first, heating to 500°C at a rate of 2°C / min and keeping at that temperature for 3 h; then heating to 700°C at a rate of 2°C / min and keeping at that temperature for 1 h; then heating to 1350°C at a rate of 8°C / min and keeping at that temperature for 2 h; finally, gas phase rapid cooling to room temperature to obtain cemented carbide.

[0044] The cutting edge of the cemented carbide blade is processed into an R angle to obtain a cemented carbide tool.

[0045] Example 3 A cemented carbide consisting of the following components: 15 parts by weight of a binder, specifically nickel powder with an average particle size of 0.5 μm; 3 parts by weight of a regulator, consisting of vanadium carbide, ruthenium and tantalum carbide in a mass ratio of 5:8:10; wherein the average particle size of the vanadium carbide powder is 1 μm, the average particle size of the ruthenium powder is 20 nm, and the average particle size of the tantalum carbide powder is 500 nm; 82 parts by weight of tungsten carbide powder, with an average particle size of 0.6 μm.

[0046] The preparation method of the above-mentioned cemented carbide is: (1) Ball milling: n-hexane is used as the medium, the ball milling speed is 40r / min, and the total ball milling time is 20h. During ball milling, according to the above components, tungsten carbide, binder and tungsten carbide grinding balls with a diameter of 3mm are first added, and ball milling is carried out for 6h; then vanadium carbide is added and ball milling is carried out for 2h; then ruthenium, tantalum carbide and tungsten carbide grinding balls with a diameter of 0.4mm are added, and finally 2wt% paraffin wax is added and ball milling is carried out for 12h.

[0047] (2) Drying and granulation: conventional spray drying method is used.

[0048] (3) Pressing: Pressing into a blade shape using conventional methods.

[0049] (4) Hydrogen sintering: The sintering steps are as follows: first, heating to 500°C at a rate of 5°C / min and keeping at that temperature for 2 h; then heating to 700°C at a rate of 5°C / min and keeping at that temperature for 0.5 h; then heating to 1500°C at a rate of 13°C / min and keeping at that temperature for 1 h; finally, gas phase rapid cooling to room temperature to obtain cemented carbide.

[0050] The cutting edge of the cemented carbide blade is processed into an R angle to obtain a cemented carbide tool.

[0051] Example 4 The difference from Example 1 is that the regulator is vanadium carbide, ruthenium and tantalum carbide in a mass ratio of 1:5:10. The details are as follows: A cemented carbide consisting of the following components: 10 parts by weight of a binder, specifically cobalt powder with an average particle size of 1 μm; 2 parts by weight of a regulator, consisting of vanadium carbide, ruthenium and tantalum carbide in a mass ratio of 1:5:10; wherein the average particle size of the vanadium carbide powder is 3 μm, the average particle size of the ruthenium powder is 80 nm, and the average particle size of the tantalum carbide powder is 600 nm; 88 parts by weight of tungsten carbide powder, with an average particle size of 0.8 μm.

[0052] The preparation method is the same as Example 1.

[0053] Example 5 The difference from Example 1 is that the average particle size of the vanadium carbide powder is lower than the preferred range, which is 0.5 μm. The details are as follows: A cemented carbide consisting of the following components: 10 parts by weight of a binder, specifically cobalt powder with an average particle size of 1 μm; 2 parts by weight of a regulator, consisting of vanadium carbide, ruthenium and tantalum carbide in a mass ratio of 4:7:10; wherein the average particle size of the vanadium carbide powder is 0.5 μm, the average particle size of the ruthenium powder is 80 nm, and the average particle size of the tantalum carbide powder is 600 nm; 88 parts by weight of tungsten carbide powder, with an average particle size of 0.8 μm.

[0054] The preparation method is the same as Example 1.

[0055] Example 6 The difference from Example 1 is that the average particle size of the ruthenium powder is higher than the preferred range, which is 0.8 μm. The details are as follows: A cemented carbide consisting of the following components: 10 parts by weight of a binder, specifically cobalt powder with an average particle size of 1 μm; 2 parts by weight of a regulator, consisting of vanadium carbide, ruthenium and tantalum carbide in a mass ratio of 4:7:10; wherein the average particle size of the vanadium carbide powder is 3 μm, the average particle size of the ruthenium powder is 0.8 μm, and the average particle size of the tantalum carbide powder is 600 nm; 88 parts by weight of tungsten carbide powder, with an average particle size of 0.8 μm.

[0056] The preparation method is the same as Example 1.

[0057] Example 7 The difference from Example 1 is that the particle sizes of the various components of the regulator are the same, and the average particle sizes of the vanadium carbide powder, ruthenium powder, and tantalum carbide powder are all 0.8 μm. A cemented carbide consisting of the following components: 10 parts by weight of a binder, specifically cobalt powder with an average particle size of 1 μm; 2 parts by weight of a regulator, composed of vanadium carbide, ruthenium and tantalum carbide in a mass ratio of 4:7:10; wherein the average particle size of the vanadium carbide powder, ruthenium powder and tantalum carbide powder is 0.8 μm; 88 parts by weight of tungsten carbide powder, with an average particle size of 0.8 μm.

[0058] The preparation method is the same as Example 1.

[0059] Example 8 The difference from Example 1 is that in step (1), only tungsten carbide grinding balls with a diameter of 3 mm are used for ball milling. The details are as follows: A cemented carbide consisting of the following components: 10 parts by weight of a binder, specifically cobalt powder with an average particle size of 1 μm; 2 parts by weight of a regulator, consisting of vanadium carbide, ruthenium and tantalum carbide in a mass ratio of 4:7:10; wherein the average particle size of the vanadium carbide powder is 3 μm, the average particle size of the ruthenium powder is 80 nm, and the average particle size of the tantalum carbide powder is 600 nm; 88 parts by weight of tungsten carbide powder, with an average particle size of 0.8 μm.

[0060] The preparation method of the above-mentioned cemented carbide is: (1) Ball milling: n-hexane is used as the medium, the ball milling speed is 30r / min, and the total ball milling time is 30h. During ball milling, tungsten carbide, binder and tungsten carbide grinding balls with a diameter of 3mm are first added according to the above components, and ball milling is performed for 8h; then vanadium carbide is added and ball milling is performed for 3h; then ruthenium and tantalum carbide are added, and finally 2wt% paraffin wax is added and ball milling is performed for 19h.

[0061] (2) Drying and granulation: conventional spray drying method is used.

[0062] (3) Pressing: Pressing into a blade shape using conventional methods.

[0063] (4) Hydrogen sintering: The sintering steps are as follows: first, heating to 500°C at a rate of 3°C / min and keeping at that temperature for 2 h; then heating to 700°C at a rate of 4°C / min and keeping at that temperature for 0.5 h; then heating to 1400°C at a rate of 10°C / min and keeping at that temperature for 1 h; finally, gas phase rapid cooling to room temperature to obtain cemented carbide.

[0064] The cutting edge of the cemented carbide blade is processed into an R angle to obtain a cemented carbide tool.

[0065] Example 9 The difference from Example 1 is that the rate of heating the hydrogen sintering to 700°C in step (4) is too fast, at 8°C / min. The details are as follows: A cemented carbide consisting of the following components: 10 parts by weight of a binder, specifically cobalt powder with an average particle size of 1 μm; 2 parts by weight of a regulator, consisting of vanadium carbide, ruthenium and tantalum carbide in a mass ratio of 4:7:10; wherein the average particle size of the vanadium carbide powder is 3 μm, the average particle size of the ruthenium powder is 80 nm, and the average particle size of the tantalum carbide powder is 600 nm; 88 parts by weight of tungsten carbide powder, with an average particle size of 0.8 μm.

[0066] The preparation method of the above-mentioned cemented carbide is: (1) Ball milling: n-hexane was used as the medium, the ball milling speed was 30 r / min, and the total ball milling time was 30 h. During ball milling, tungsten carbide, binder and tungsten carbide grinding balls with a diameter of 3 mm were first added according to the above components, and ball milling was performed for 8 h; then vanadium carbide was added and ball milling was performed for 3 h; then ruthenium, tantalum carbide and tungsten carbide grinding balls with a diameter of 0.4 mm were added, and finally 2 wt% paraffin wax was added and ball milling was performed for 19 h.

[0067] (2) Drying and granulation: conventional spray drying method is used.

[0068] (3) Pressing: Pressing into a blade shape using conventional methods.

[0069] (4) Hydrogen sintering: The sintering steps are as follows: first, heating to 500°C at a rate of 3°C / min and keeping at that temperature for 2 h; then heating to 700°C at a rate of 8°C / min and keeping at that temperature for 0.5 h; then heating to 1400°C at a rate of 10°C / min and keeping at that temperature for 1 h; finally, gas phase rapid cooling to room temperature to obtain cemented carbide.

[0070] The cutting edge of the cemented carbide blade is processed into an R angle to obtain a cemented carbide tool.

[0071] Example 10 The difference from Example 1 is that the rate of heating the hydrogen sintering to 1400°C in step (4) is too slow, at 5°C / min. The details are as follows: A cemented carbide consisting of the following components: 10 parts by weight of a binder, specifically cobalt powder with an average particle size of 1 μm; 2 parts by weight of a regulator, consisting of vanadium carbide, ruthenium and tantalum carbide in a mass ratio of 4:7:10; wherein the average particle size of the vanadium carbide powder is 3 μm, the average particle size of the ruthenium powder is 80 nm, and the average particle size of the tantalum carbide powder is 600 nm; 88 parts by weight of tungsten carbide powder, with an average particle size of 0.8 μm.

[0072] The preparation method of the above-mentioned cemented carbide is: (1) Ball milling: n-hexane was used as the medium, the ball milling speed was 30 r / min, and the total ball milling time was 30 h. During ball milling, tungsten carbide, binder and tungsten carbide grinding balls with a diameter of 3 mm were first added according to the above components, and ball milling was performed for 8 h; then vanadium carbide was added and ball milling was performed for 3 h; then ruthenium, tantalum carbide and tungsten carbide grinding balls with a diameter of 0.4 mm were added, and finally 2 wt% paraffin wax was added and ball milling was performed for 19 h.

[0073] (2) Drying and granulation: conventional spray drying method is used.

[0074] (3) Pressing: Pressing into a blade shape using conventional methods.

[0075] (4) Hydrogen sintering: The sintering steps are as follows: first, heating to 500°C at a rate of 3°C / min and keeping at that temperature for 2 h; then heating to 700°C at a rate of 4°C / min and keeping at that temperature for 0.5 h; then heating to 1400°C at a rate of 5°C / min and keeping at that temperature for 1 h; finally, gas phase rapid cooling to room temperature to obtain cemented carbide.

[0076] The cutting edge of the cemented carbide blade is processed into an R angle to obtain a cemented carbide tool.

[0077] Comparative Example Comparative Example 1 The difference from Example 1 is that no tantalum carbide is added to the regulator, and the regulator is vanadium carbide and ruthenium in a mass ratio of 4:7.

[0078] Comparative Example 2 The difference from Example 1 is that no ruthenium is added to the regulator, and the regulator is vanadium carbide and tantalum carbide in a mass ratio of 4:10.

[0079] Comparative Example 3 The difference from Example 1 is that no vanadium carbide is added to the regulator, and the regulator is ruthenium and tantalum carbide in a mass ratio of 7:10.

[0080] Comparative Example 4 The difference from Example 1 is that ruthenium in the regulator is replaced by rhenium, and the regulator is vanadium carbide, rhenium and tantalum carbide in a mass ratio of 4:7:10.

[0081] Comparative Example 5 The difference from Example 1 is that there is an excess of tantalum carbide in the regulator, and the regulator is vanadium carbide, ruthenium and tantalum carbide in a mass ratio of 4:7:12.

[0082] Comparative Example 6 The difference from Example 1 is that ruthenium is excessive in the regulator, and the regulator is vanadium carbide, ruthenium and tantalum carbide in a mass ratio of 4:10:10.

[0083] Performance Testing The performance test of the cemented carbide cutting tools prepared in each embodiment and comparative example was carried out, and the test method was based on the existing standards, wherein the Vickers hardness test was based on GB T 7997-2014, and the test force was 294.2N (30kgf); the cutting test conditions were: workpiece QT500, cutting speed 320m / min, feed 0.12mm / rev, cutting depth 1mm, cutting width 50mm, cutting method dry milling, and the average wear of the blade back face Vb exceeding 0.3mm or any blade wear Vbmax or chipping exceeding 0.3mm was selected as the life judgment standard. The results are shown in the following table. <![CDATA[Vickers hardness (kgf / mm 2 )]]> <![CDATA[Fracture toughness K IC (MN / m 3 / 2 )]]> Milling life (min) Example 1 1851 9.7 65 Example 2 1840 9.6 64 Example 3 1843 9.5 62 Example 4 1800 9.2 58 Example 5 1730 9.0 55 Example 6 1750 9.1 56 Example 7 1710 8.7 51 Example 8 1825 9.3 59 Example 9 1720 8.9 52 Example 10 1724 8.6 53 Comparative Example 1 1650 9.0 42 Comparative Example 2 1660 8.2 41 Comparative Example 3 1617 9.3 38 Comparative Example 4 1824 9.1 57 Comparative Example 5 1600 9.3 50 Comparative Example 6 1826 9.0 60

[0084] As can be seen from the above table, the cemented carbide tools made in each embodiment of the present invention have excellent hardness and toughness and a long service life. Embodiments 1-3 are the best embodiments within the most preferred range of the present invention. Compared with Embodiment 1: In Example 4, the proportion of each component in the regulator is within the preferred range but does not fall within the optimal range, and the overall performance is reduced. In Example 5, the particle size of the vanadium carbide powder is small, even lower than that of tantalum carbide and tungsten carbide, resulting in a decrease in performance. It is speculated that because the particle size affects the dissolution rate, vanadium carbide is dissolved and precipitated before tantalum carbide and tungsten carbide. After the vanadium carbide solvent is precipitated, it plays a hardening and densifying role early, which is not conducive to the subsequent uniform precipitation of tungsten carbide. In Example 6, the particle size of the ruthenium powder is large, even higher than that of tantalum carbide, and close to that of tungsten carbide. The ruthenium powder cannot be dissolved and precipitated preferentially, and the effect of inhibiting the growth of tungsten carbide grains (especially abnormal growth) and promoting the transformation of the metastable α-Co of cobalt to the room temperature stable state ε-Co is also greatly reduced, resulting in a decrease in performance. In Example 7, the particle size of each powder in the regulator is consistent with that of tungsten carbide, and there is no difference in particle size. The effect is not as good as that of Examples 5 and 6, indicating that the particle size difference set by the present invention is indeed helpful in improving the performance of the alloy.

[0085] Comparative Examples 1-3 lack one of tantalum carbide, ruthenium, and vanadium carbide, respectively, and Comparative Example 4 replaces ruthenium with rhenium, but the effects are not as good as those of Example 1, indicating that the three cooperate with each other to have a significant gain effect. In Comparative Example 5, tantalum carbide is excessive, because tantalum has low hardness and rich ductility, excessive addition of tantalum carbide will reduce the hardness of the alloy. In Comparative Example 6, ruthenium is excessive, the alloy performance is also reduced, and the cost is increased, so the amount of ruthenium added can be within an appropriate range.

[0086] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.

Claims

1. A cemented carbide, characterized in that: Each 100 parts by mass contains: 8-15 parts of binder; 0.5-3 parts of a regulator, consisting of vanadium carbide, ruthenium and tantalum carbide in a mass ratio of (1-6):(5-8):10; The balance is tungsten carbide.

2. A cemented carbide according to claim 1, characterized in that: The mass ratio of vanadium carbide, ruthenium and tantalum carbide is (2-5):(6-8):

10.

3. A cemented carbide according to claim 1 or 2, characterized in that: The average particle size of tungsten carbide powder is 0.6-1μm, the particle size of ruthenium is lower than that of tungsten carbide, the particle size of tantalum carbide is similar to that of tungsten carbide, and the particle size of vanadium carbide is larger than that of tungsten carbide.

4. A cemented carbide according to claim 3, characterized in that: The average particle size of vanadium carbide powder is 1-5 μm, the average particle size of ruthenium powder is 20-100 nm, and the average particle size of tantalum carbide powder is 500-800 nm.

5. A cemented carbide according to claim 1, characterized in that: The binder is selected from one or more of Co, Ni and Mo powders.

6. The method for preparing the cemented carbide according to any one of claims 1 to 5, characterized in that: The following steps are involved: Ball milling, dry granulation, compression molding and hydrogen sintering.

7. The method for preparing a cemented carbide according to claim 6, characterized in that: The ball milling medium is n-hexane, the ball milling speed is 80-100 r / min, and the ball milling time is 20-40 h.

8. The method for preparing a cemented carbide according to claim 7, characterized in that: During ball milling, first add tungsten carbide, a binder and tungsten carbide grinding balls with a diameter of 2-5 mm, and ball mill for 6-10 hours; then add vanadium carbide and ball mill for 2-4 hours; finally add ruthenium, tantalum carbide and tungsten carbide grinding balls with a diameter of 0.2-0.5 mm, and ball mill.

9. A method for preparing a cemented carbide according to claim 6, 7 or 8, characterized in that: The sintering steps are as follows: (1) Raise the temperature to 500 °C at a rate of 2-5 °C / min and keep at this temperature for 2-3 h; (2) Raise the temperature to 700 °C at a rate of 2-5 °C / min and keep at this temperature for 0.5-1 h; (3) Raise the temperature to 1350-1500 °C at a rate of 8-13 °C / min and keep at this temperature for 1-2 h; (4) Quickly cool to room temperature.

10. Use of the cemented carbide according to any one of claims 1 to 5 in cemented carbide tools, characterized in that: Cemented carbide tools include cemented carbide milling tools and cemented carbide turning tools.

Citation Information

Patent Citations

  • Rock drill bits

    CN109790076B

Cited By

  • Preparation method of hard alloy

    CN121802263A

  • A method for producing a cemented carbide

    CN121802263B